The cytokinesis-block micronucleus (CBMN) assay in human populations exposed to styrene: A systematic review and meta-analysis - Costa, S (2016)
Styrene is a building-block of several compounds used in a wide array of materials and products. The most important human exposure to this substance occurs in industrial settings, especially among reinforced-plastics industry workers. The effect of occupational exposure to styrene on cytogenetics biomarkers has been previously reviewed with positive association observed for chromosomal aberrations, and inconclusive data for the micronucleus assay. Some limitations were noted in those studies, including inadequate exposure assessment and poor epidemiological design. Furthermore, in earlier studies micronuclei frequency was measured with protocols not as reliable as cytokinesis-block micronucleus (CBMN) assay. Aim of the present systematic review and meta-analysis is to investigate genomic instability and DNA damage as measured by the CBMN assay in lymphocytes of subjects exposed to styrene. A total of 11 studies published between 2004 and 2012 were included in the meta-analysis encompassing 479 styrene-exposed workers and 510 controls. The quality of each study was estimated by a quality scoring system which ranked studies according to the consideration of major confounders, exposure characterization, and technical parameters. An overall increase of micronuclei frequencies was found in styrene-exposure workers when compared to referents (meta-MR 1.34; 95% CI 1.18-1.52), with significant increases achieved in six individual studies. The consistency of results in individual studies, the independence of this result from major confounding factors and from the quality of the study strengthens the reliability of risk estimates and supports the use of the CBMN assay in monitoring genetic risk in styrene workers.